Efektivitas Penerapan E-Government Dalam Mewujudkan Smart City Di Kabupaten Tapanuli Selatan - Indra Syahputra Marpaung; Nurbaya Harianja; Muallim Hasibuan; Rosina Harahap (Concept: Journal of Social Humanities and Education, 2023)
In the current era of globalization and digital, fast, precise and accurate information services are needed. One of the technologies that must be applied in government agencies is the implementation of e-government which refers to the development of national e-government, and is adapted to the conditions that exist in each government agency. The aim of this e-government is to improve the quality of service and especially to realize the smart city which is currently being discussed. One of the districts that has recently implemented a smart city is the South Tapanuli district. So that in this study an analysis of the application of e-government in realizing smart cities will be carried out with the aim of knowing the process of implementing e-government policies, implementing smart cities that focus on the community, and to find out the obstacles or obstacles in the implementation of e-government. The results of the study explain that the implementation of e-government in South Tapanuli district is indeed very effective in realizing smart cities in the midst of increasingly sophisticated technological developments. This is shown by the achievement of smart city aspects, although not optimal. In the implementation of e-government there are still a number of weaknesses, obstacles and challenges because the implementation in South Tapanuli district is still relatively new. These obstacles include the inadequate availability of human resources, the level of public capacity regarding e-government is still very low. Supporting factors for e-government implementation are full government support through regulations and established financial support.